Pelatihan Pengolahan Hasil Pertanian dan Pemasaran Digital sebagai Produktivitas UMKM untuk Mengurangi Tingkat Pengangguran di SMK Pertanian Lubuklinggau - Widya Analisa; Syabawaihi Syabawaihi; Rizka Aulia; Muhamad Fadli; Shinta Aprilisa; M. Nejatullah Sidqi (LP4MK STKIP PGRI Lubuklinggau, 2025)
This community service activity aims to enhance the entrepreneurial skills of students at SMK Pertanian Lubuklinggau through training in agricultural product processing and digital marketing. It is expected to reduce the unemployment rate by creating self-employment opportunities based on local potential. The activity was carried out in three stages: preparation, implementation, and evaluation. The implementation phase lasted for two days and included training on processing local agricultural products and digital marketing using social media and marketplace platforms. Evaluation was conducted through pre-tests, post-tests, and interviews. The training resulted in a significant improvement in students’ knowledge and skills. Participants were able to produce processed agricultural products such as mackerel bone crackers and durian seed flour, and market them through digital media. High enthusiasm and increased entrepreneurial motivation were evident throughout the program. The training program proved effective in increasing the productivity and competitiveness of vocational school graduates. This activity supports the development of agroindustry-based MSMEs and opens up self-employment opportunities for students. The school is committed to continuing the program by integrating it into the curriculum and forming student entrepreneurship groups.